1987
DOI: 10.3164/jcbn.2.83
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cyclic and Continuous Total Enteral Nutrition on Circadian Cortisol Rhythm

Abstract: To clarify relationships between the pattern of diet intake and the circadian adrenocortical rhythm, we measured plasma cortisol levels at circadian intervals in two groups of patients who had been receiving total enteral nutrition (TEN) for about 11 days: one group was given a liquid diet intraduodenally and continuously (continuous TEN), whereas the other received their nutrition discontinuously from 0700-2300 h every day (cyclic TEN). In patients with cyclic TEN there was a clear cortisol rhythm with a peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Our previous results (2,3) clearly showed that the phase of the cortisol rhythm was shifted by changing the daily pattern of diet infusion, suggesting a synchronizing effect of food intake on the adrenocortical rhythm in man as well as in laboratory animals. To extend this view and to confirm the relationship between diet intake and circadian rhythm of other physiological activities in man, in this study we examined 24-h patterns of body temperature and urinary excretions in the same patients as in the previous study (3): that is, they were kept under a schedule of either continuous or cyclic TEN.…”
mentioning
confidence: 83%
“…Our previous results (2,3) clearly showed that the phase of the cortisol rhythm was shifted by changing the daily pattern of diet infusion, suggesting a synchronizing effect of food intake on the adrenocortical rhythm in man as well as in laboratory animals. To extend this view and to confirm the relationship between diet intake and circadian rhythm of other physiological activities in man, in this study we examined 24-h patterns of body temperature and urinary excretions in the same patients as in the previous study (3): that is, they were kept under a schedule of either continuous or cyclic TEN.…”
mentioning
confidence: 83%